Tinjauan Maqāṣid Asy-Syarīꜥah Terhadap Pengangkatan Anak Tanpa Penetapan Pengadilan (Studi Desa Pajomblangan Kec. Kedungwuni Kab. Pekalongan).: Maqāṣid Asy-Syarīꜥah's Review of Child Adoption Without Court Determination (Study in Pajomblangan Village, Kedungwuni, Pekalongan) - Aristiani, Risma; Fauzan, Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
In Indonesia, the process of adopting a child is regulated in Government Regulation no. 54 of 2007 concerning the Implementation of Child Adoption where the child adoption process must be carried out through a court decision to obtain legal certainty and legality. However, in Pajomblangan Village, Kec. In Kedungwuni there are still couples who do not legalize the adoption in court. Apart from that, in adoption, consideration of the benefit of the child is also important. This research is a type of field research using a juridical-empirical approach. Research data was obtained through observation, interviews and documentation using primary legal data sources and secondary legal data. Data analysis used used descriptive analysis methods. The results of this research indicate that the adoption of children by couples in Pajomblangan Village was carried out only based on agreement and willingness between the biological parents and adoptive parents without the legality of a court decision. Apart from that, in the population certificate (birth certificate and family card), the child is registered and has the status of being the biological child of the adoptive parents. If viewed from the maqāṣid asy-syarīꜥah, the practice of adoption in Pajomblangan Village can fulfill 2 (two) benefits from the 5 main maqāṣid asy-syarīꜥah at the level al-Ḍharūriyyāt, namely the maintenance of religion (hifẓ ad-dīn) and the maintenance of reason (hifẓ al-aql)